Encouraging student learning of control by embedding freedom into the curriculum: student perspectives and products. Issue 1 (July 2017) - Rossiter, J.A.; Barnett, L.; Cartwright, E.; Patterson, J.; Shorten, N.; Taylor, J.
Abstract: Many engineering students have little inherent interest in control topics and struggle to relate these to their career goals. This paper looks at a novel mechanism for encouraging students to take more ownership of their learning of control topics and, by doing so, improve engagement and learning. Consequently it also fits well into research led teaching philosophies. The main focus here is on the student products for an assignment the author designed in the curriculum which challenged students to develop a learning resource. The paper includes description of one of these student generated resources, which could be shared with or used by the community, and the personal experiences and reflections of the students who produced this resource.